Improving the Security of Workflow-based System using Multiple XML Digital Signature (International Journal of Engineering and Computer Science, 2015)
Private companies and Government Organizations all around the world make huge investments for the automation of their processes and in the management of the electronic documentation in recent times. The main requirement in the management of digital documentation is its equivalence, from a legal perspective, to paperwork, affixing a signature on a digital document is the fundamental principle; which are based the main processes of authorization and validation, apart from the specific area of application. Main benefits for introduction of digital signing processes are cost reduction and complete automation of documental workflow, including authorization and validation phases. In essence, digital signatures allow you to replace the approval process on paper, slow and expensive, with fully digital system, faster and cheaper.